2012
DOI: 10.1002/mats.201100111
|View full text |Cite
|
Sign up to set email alerts
|

Small‐Angle Scattering From Branched Polymers

Abstract: The single-polymer form factor is determined for branched polymers using a scaling argument in order to recover the low-Q Porod exponent characteristic of the overall structure. The high-Q Porod exponent characterizes the local branching structure. An alternative approach based on a high-Q expansion contains information about functionality, branch length and branch content. The specific case of a starburst dendrimer for which the form factor is known is discussed. The model predictions are compared to small-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 14 publications
(13 reference statements)
2
62
1
Order By: Relevance
“…Cylindrical network junctions displaying a q 22 decay in the mid-q regime followed by a plateau at low-q [25] are also not observed. Hammouda [26] has shown that the form factor of branched polymers exhibits a broad shoulder and a decay with q Àc , 2 c 1, again incompatible with our experimental curves. Rather, the q 24 scaling suggests the dominance of scattering from interfaces.…”
Section: Scattering Of Natural Plaquescontrasting
confidence: 65%
“…Cylindrical network junctions displaying a q 22 decay in the mid-q regime followed by a plateau at low-q [25] are also not observed. Hammouda [26] has shown that the form factor of branched polymers exhibits a broad shoulder and a decay with q Àc , 2 c 1, again incompatible with our experimental curves. Rather, the q 24 scaling suggests the dominance of scattering from interfaces.…”
Section: Scattering Of Natural Plaquescontrasting
confidence: 65%
“…A logical property of this comb approximation is that the longest side arm length cannot exceed half the backbone length, as a consequence of identifying the backbone as the longest end‐to‐end distance. Note finally that what we have called “backbone” here, is in fact identical to the “minimum path” as discussed by Hammouda …”
Section: Branching Topologiesmentioning
confidence: 65%
“…Here we will compare P −1 (θ) behavior of realistic ldPE topologies with the typical terminal branching topologies associated with the Zimm and Stockmayer theory. First, we explore the asymptotic behavior of P (θ), since this offers an interesting comparison to a similar exercise by Hammouda . Second, we will present scattering function results for terminally branched molecules, the topology for which Zimm and Stockmayer have derived their famous contraction factor formula.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations